The Internal Audit Function and Financial Performance in the Telecommunication Companies - Rosette Kyoshabire (Uganda Christian University, 2024)
apter 1 represents the background of the study i.e. for the topic, it also states the problem of the study and its objectives and the purpose .it presents the research questions, area scope of the study and its significance. Chapter 2 represents the literature-reviewed literature on internal auditing and financial performance and the understanding of different scholars of authors on such variables Chapter 3 represents the research methodology, it comprises of the research design, the study population sample size and method, sources of data collection instruments, the data quality which involves reliability and validity and methods of data presentation. The research was descriptive in nature whereby interview and questionnaires were used during data collection. Chapter 4 gives out the findings of the research in reference to the research questions; presentation of the data was done through tabulations and pie charts for easy understanding The last chapter that is five presents and summarize data in a more precise way. In addition, provides the recommendations and conclusions of the study. The researcher therefore hopes that at the completion of the research, it will improve financial performance of Airtel Uganda